Knowledge of Antimicrobial Resistance and Associated Factors Among Health Professionals at the University of Gondar Specialized Hospital: Institution-Based Cross-Sectional Study - Simegn, Wudneh; Dagnew, Baye; Weldegerima, Berhanemeskel; Dagne, Henok (Frontiers in Public Health, 2022)
Background Antimicrobial resistance is one of the many health challenges worldwide, particularly in resource-limited countries like Ethiopia. Increasing knowledge of health professionals can reduce the occurrence of antimicrobial resistance. In this study, we determined the antimicrobial resistance knowledge and examined the associated factors among the University of Gondar Hospital health professionals. Methods An institution-based cross-sectional survey was carried out. The samples were randomly recruited. Statistical analysis was performed by using the statistical package for social sciences (SPSS) version 20 after entering the data using Epidemiological information (Epi-Info). To identify associated factors, the authors executed binary logistic regression and multivariate analysis wherein the statistical significance was decided at p < 0.05. Results Four hundred and twelve health professionals with ages ranging from 20-60 years and mean age of 29.9 years took part in the study. Fifty-three-point-four percent of participants were males. The majority of the total respondents (84.7%, 95% CI: 80.08–88.30) had good knowledge of antimicrobial resistance. It was found that being male (AOR = 1.94, 95% CI: 1.10, 3.52), a work experience of 6–10 years (AOR = 2.45, 95% CI: 1.28, 4.68), having 30–38working hours per week (AOR = 3.93, 95% CI: 1.38, 5.11), and antibiotic intake (AOR = 3.71, 95% CI: 1.75, 7.87) were significant factors of antimicrobial resistance knowledge. Conclusion In the current study, about 84.5% of health professionals had good knowledge of antimicrobial resistance. Reducing working hours per week and increasing the experience of workers are recommended to increase the knowledge on AMR.